3(2x-4)-2(2x+3)=

Simple and best practice solution for 3(2x-4)-2(2x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-4)-2(2x+3)= equation:


Simplifying
3(2x + -4) + -2(2x + 3) = 0

Reorder the terms:
3(-4 + 2x) + -2(2x + 3) = 0
(-4 * 3 + 2x * 3) + -2(2x + 3) = 0
(-12 + 6x) + -2(2x + 3) = 0

Reorder the terms:
-12 + 6x + -2(3 + 2x) = 0
-12 + 6x + (3 * -2 + 2x * -2) = 0
-12 + 6x + (-6 + -4x) = 0

Reorder the terms:
-12 + -6 + 6x + -4x = 0

Combine like terms: -12 + -6 = -18
-18 + 6x + -4x = 0

Combine like terms: 6x + -4x = 2x
-18 + 2x = 0

Solving
-18 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 2x = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 2x = 0 + 18
2x = 0 + 18

Combine like terms: 0 + 18 = 18
2x = 18

Divide each side by '2'.
x = 9

Simplifying
x = 9

See similar equations:

| 24=-6x-4(0.25x-2) | | 21.792/0.96= | | 3x+72=180 | | 30-11=c | | y-96=23.75x-2+16y | | x+30=180 | | (-4.2)(-6.8)= | | 7n+8=78 | | 15-(-4)=d | | 10x+4=11x+2 | | (-16)-(-42)= | | 2x^2-40=8x^2 | | 100+x=180 | | x-3x+2=2 | | 9b=-144 | | 8(-6)+10y=80 | | 2x^2-30=2 | | 2p-35=-7(6p+5) | | a*a+a= | | 8x+8=3x+3 | | 640x^2-10=0 | | 640x^2-30=2 | | -9(-8.0526)-3y=27 | | 10x^2-640=0 | | -9c+5c= | | .666666x=.5333333 | | 2x+4y=-5 | | -2x-5x+3x= | | -3x-9=-0.88+8 | | -3v^2-5v+24=0 | | (3x-2)(4x+1)= | | 145=10x-8 |

Equations solver categories